Brain death: Is it an appropriate term? - J. Iriarte; J.A. Palma; E. Kufoy; M.J. de Miguel (Neurología (English Edition), 2012)
Introduction: Brain death is generally accepted as a concept to indicate death. It was introduced about 40 years ago, and it was considered the ideal situation for donation of organs. Material and methods: During this time, however, there have been problems in the understanding of this concept both in the medical profession and in the general population. University students from medical and non-medical schools were tested for their understanding of this concept. Results: Our results show that less than one third of the non-medical students identified brain death as death. The data from the medical students changed as they progressed through their studies, but only 2/3 of the graduating medical class believed that brain death is death. Conclusion: Similar results have been seen in other universities around the world, and a renewed effort on the re-education of the concept of brain death may be worthwhile. Although we cannot extrapolate these results to the general population, the confusion is probably similar; hence an effort should be made to solve this problem. Resumen: Objetivo: “Muerte cerebral” es un término generalmente aceptado para indicar la muerte. Fue introducido hace más de 40 años, y, desde entonces, se considera la situación ideal para la donación de órganos. Sin embargo, existen serios problemas con respecto a la comprensión de este concepto, tanto en profesionales médicos como en la población general. Métodos: Se realizó una encuesta a estudiantes universitarios de facultades médicas y no médicas para comprobar la interpretación del concepto de muerte cerebral. Resultados: Menos de un tercio de los estudiantes no médicos identificaron claramente muerte cerebral con muerte. Los datos en estudiantes de Medicina diferían a medida que los cursos eran más avanzados, pero sólo dos tercios de los alumnos de último curso de Medicina pensaban que la muerte cerebral equivalía a muerte. Resultados similares se han encontrado en universidades de otros países, siendo necesario un mayor esfuerzo en la docencia del concepto de muerte cerebral. Conclusiones: Los resultados de este trabajo muestran la confusión existente entre universitarios a la hora de interpretar el término “muerte cerebral”; aunque esta confusión no es extrapolable a la población general es probable que la confusión en la población no sea menor. Por ello, dada la importancia del tema, deberían plantearse soluciones para resolver esta confusión, bien explicando mejor el término o modificando la terminología. Keywords: Brain death, Misunderstanding, Palabras clave: Muerte cerebral, Malinterpretación